2011
DOI: 10.1002/chir.20982
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Friedel–Crafts reaction of indoles with trifluoroacetaldehyde catalyzed by Cinchona alkaloids

Abstract: The first direct asymmetric synthetic preparation of trifluoro-1-(indol-3-yl)ethanols (TFIEs) is described by an enantioselective organocatalytic method from indoles and inexpensive trifluoroacetaldehyde methyl hemiacetal. The reaction is catalyzed by hydroquinine to produce TFIEs in an almost quantitative yield and with enantioselectivities up to 75% at room temperature. The enantioselectivity is strongly dependent on the concentration of substrates and catalyst due to the competitive noncatalyzed reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…In some cases, we used our own earlier methods, [18–20] in the case of the remaining products literature analogies were applied. [21] A few selected chiral compounds were also synthesized by a cinchona alkaloid-catalyzed hydroxy-alkylation, [20, 22] to confirm the effect of inhibitor stereochemistry on the anti-aggregation potency, especially since in our earlier report only the anti-fibril effect was described. [17] …”
Section: Resultsmentioning
confidence: 99%
“…In some cases, we used our own earlier methods, [18–20] in the case of the remaining products literature analogies were applied. [21] A few selected chiral compounds were also synthesized by a cinchona alkaloid-catalyzed hydroxy-alkylation, [20, 22] to confirm the effect of inhibitor stereochemistry on the anti-aggregation potency, especially since in our earlier report only the anti-fibril effect was described. [17] …”
Section: Resultsmentioning
confidence: 99%
“…39,40 The N-substituted product can be obtained under kinetic control using a strong base or metal mediated reactions. 25 However, our recent mechanistic and DFT investigations showed that the outcome of this hydroxyalkylation reaction is highly dependent on the choice of the reaction conditions, especially the selection of the solvent.…”
Section: Resultsmentioning
confidence: 99%
“…3‐Substituted‐2‐phenylindoles have been recognized as privileged structures in medicinal chemistry with a broad biological activity profile for G protein‐coupled receptor modulation . The available synthetic methods for the installation of the stereogenic, (trifluoromethyl)hydroxymethyl group at position 3 of indoles are presently limited to a radical cross‐dehydrogenative coupling and an enantioselective Friedel–Crafts reaction of indoles with trifluoroacetaldehyde, catalyzed by cinchona alkaloids . The latter approach, however, provides only very low enantioselectivities.…”
Section: Methodsmentioning
confidence: 99%